Arsenic promotes the COX2/PGE2–SOX2 axis to increase the malignant stemness properties of urothelial cells. Issue 1 (14th February 2018) - Ooki, Akira; Begum, Asma; Marchionni, Luigi; VandenBussche, Christopher J.; Mao, Shifeng; Kates, Max; Hoque, Mohammad Obaidul
Abstract : Chronic arsenic exposure is associated with the development of urothelial carcinoma of the bladder (UCB). To elucidate the contribution of arsenic exposure to urothelial cancer stem cell (CSC) generation, we established an in vitro stepwise malignant model transformed by chronically exposing human urothelial cells to arsenic. Using this model, we found that chronic arsenic exposure endows urothelial cells with malignant stemness properties including increased expression of stemness‐related factors such as SOX2, sphere formation, self‐renewal, invasion and chemoresistance. SOX2 was gradually and irreversibly overexpressed in line with acquired sphere‐forming and self‐renewal abilities. Following gene set enrichment analyses of arsenic‐exposed and arsenic‐unexposed cells, we found COX2 as an enriched gene for oncogenic signature. Mechanistically, arsenic‐induced COX2/PGE2 increases SOX2 expression that eventually promotes malignant stem cell generation and repopulation. In urine samples from 90 subjects exposed to arsenic and 91 control subjects, we found a significant linear correlation between SOX2 and COX2 expression and the potential of SOX2 and COX2 expression as urinary markers to detect subjects exposed to arsenic. Furthermore, the combination marker yielded a high sensitivity for UCB detection in a separate cohort. Finally, our in vitro model exhibits basal‐type molecular features and dual inhibition of EGFR and COX2 attenuated stem cell enrichment more efficiently than an EGFR inhibitor alone. In conclusion, the COX2/PGE2‐SOX2 axis promotes arsenic‐induced malignant stem cell transformation. In addition, our findings indicate the possible use of SOX2 and COX2 expression as urinary markers for the risk stratification and detection of UCB. Abstract : What's new? Environmental exposures to arsenic are associated with the development of urothelial carcinoma of the bladder (UCB). However, the molecular mechanisms of arsenic‐induced UCB remain elusive. In this study, chronic exposure to arsenic was found to induce malignant stem cell transformation in human urothelial HUC1 cells. Arsenic‐induced transformation was associated with increased expression of stemness‐related factors, including self‐renewal and invasion, and with overactivation of the COX2/PGE2–SOX2 axis. SOX2 and COX2 expression were significantly elevated in urine samples from UCB patients and may have potential as urinary markers for UCB detection and for risk assessment of arsenic exposure.